Giving Exclusive Asi In MIS Kecamatan Kindang Bulukumba District - Haerati; Safruddin; Rahmi (Lembaga Penelitian dan Pengabdian Masyarakat, Stikes Panrita Husada Bulukumba, 2018)
According to the World Health Organization (WHO), 2011 Exclusive breastfeeding is breastfeeding only to infants up to 6 months of age without additional and can be given until babies are 2 years old. Exclusive breastfeeding plays an important role in the quality and quantity during the period of brain growth that occurs from 0 to 6 months contained in exclusive breastfeeding, 80% of children's brain development starts in the womb until the age of 3 years, known as the golden period, so that exclusive breastfeeding is needed for 6 months and can be continued until the child is 2 years old. That is because breast milk contains protein, carbohydrates, fats, and minerals that babies need in a balanced amount. There is a relationship between the history of exclusive breastfeeding with the value of learning achievement. The more people who consume exclusive breastfeeding will also increase the value of learning achievement several things can increase the value of learning achievement, namely nutrition, psychology, the environment. The purpose of this study was to determine the relationship of exclusive breastfeeding with children's learning achievement. This research method uses a cross-sectional design. The sample in this study were 124 children taken by the Probability Random Sampling method with the Cluster Sampling technique. Data analysis in this study used the Mann Whitney test with a significant level of a (<0.05). The results showed that exclusive breastfeeding with learning achievement obtained a value (P = 0.005). Conclusion in this study ASI is the best food that should be given to infants because it contains almost all the nutrients needed by infants or ASI which is the liquid produced by secretions mother's breast glands. Children who are babies when getting exclusive breastfeeding are better at reading, writing, and mathematics at ages 5, 7, 11, and 14 years.